a)
[tex] - 6c - (3c + 2) = - 6c - 3c - 2 = - 9c - 2[/tex]
b)
[tex]7x - 8 - (5x + 6) = 7x - 8 - 5x - 6 = 7x - 5x - 8 - 6 = 12x - 14[/tex]
c)
[tex]9y - (8 - 3y) + 16 = 9y - 8 + 3y + 16 = 9y + 3y - 8 + 16 = 12y - 8[/tex]
d)
[tex]5x - (2 - 4x) + 8x - 7 = 5x - 2 + 4x + 8x - 7 = 5x + 4x + 8x - 2 - 7 = 17x - 9[/tex]
e)
[tex]6 - ( - 5c - 8) - 10c = 6 - 5c + 8 - 10c = - 5c - 10c + 6 + 8 = - 5c + 14[/tex]
f)
[tex] - 4(3x - 6) - 3(2 + 7x) = - 12x - 24 - 6 + ( - 21x) = - 12x - 21x - 24 - 6 = - 33x - ( - 30)[/tex]
g)
[tex]5(3z - 7) - 9( - 8z - 6) = 15z - 35 - 72z - 56 = 15z - 72z - 35 - 56 = 87z - 91[/tex]
h)
[tex]7x - 3(5x + 2) - (7 + 2x) = 7x - 15x + 6 - 7 - 2x = 7x - 15x + - 2x + 6 - 7 = 24x + 13[/tex]